1970
DOI: 10.3329/cardio.v3i1.6423
|View full text |Cite
|
Sign up to set email alerts
|

Study of Association of C-Reactive Protein with Coronary Collateral Development

Abstract: Background: In vitro studies have shown that C-reactive protein (CRP) attenuates nitric oxide production and inhibits angiogenesis, which may result in impaired collateral development. The aim of this study was to investigate the association between CRP levels and the extent of coronary collaterals. Materials and methods: A total of 100 patients who had a stenosis of >95% in any major coronary artery in angiograms were included in the study. The CRP was measured from a venous blood sample with a high-sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
3
5
0
Order By: Relevance
“…Chowdhury et al 28 found that among 4500 cases of first MI admitted into NICVD, mean age of the patients was 53±10 years.Male patients were predominant among the study population. This was consistent with previous studies in Bangladesh by which the percentage of male patients were 85-92 % 29,30 .…”
Section: Discussionsupporting
confidence: 93%
“…Chowdhury et al 28 found that among 4500 cases of first MI admitted into NICVD, mean age of the patients was 53±10 years.Male patients were predominant among the study population. This was consistent with previous studies in Bangladesh by which the percentage of male patients were 85-92 % 29,30 .…”
Section: Discussionsupporting
confidence: 93%
“…Kerner et al showed that elevated CRP levels in patients with chronic CAD are associated with decreased coronary collateral ow [26]. Similarly, it has been found in other studies that elevated CRP levels negatively affected the development of coronary collateral ow [14,27,28]. In our study, CRP levels were higher in patients with poor collateral circulation.…”
Section: Discussionsupporting
confidence: 86%
“…Increasing the HDL-C level increases endothelium-mediated vasodilation by correcting endothelial functions [13]. The C-reactive protein (CRP) level is correlated negatively with angiographic coronary collateral development [14]. Non-HDL-C is correlated with C-reactive protein (CRP), which is a reliable marker of in ammation, but LDL-C has not been shown to correlate with CRP [15].…”
Section: Introductionmentioning
confidence: 99%
“…12 While the ability of monocyte migration towards growth factor stimulation in diabetes mellitus was impaired, which contributes to poor collateralization in diabetic individuals. 14 There is also no significant difference in collateralization between STEMI and NSTEMI patients, as described in a previous study by Majumder et al 15 Thus the differences between the nature of coronary collaterals and pathophysiological process involving STEMI and NSTEMI may contribute to the result.…”
Section: Discussionmentioning
confidence: 77%